Taxpayer Enterprise Entering a Complete Accounting System and Applying VAT with a Tax Office in Luang Prabang - LUANGVILAI, Seangphavong; KEOBUALAPHETH , Soulideth; LATTANASOUVANAPHON, Champa (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
Tax receipts for the budget according to the legitimate interests of the business people contribute actively to the taxation of the State budget for the mission of preservation, national development and socio-economic development of the people This study aims to study the understanding of organization, legal entity, person of understanding, how to register tax, tax registration, tax identification, tax cancellation aimed at managing the tax distribution of business units, tax authorities, and tax authorities so, Taxpayer Enterprise Entering a Complete Accounting System and Applying VAT with a Tax Office in Luang Prabang considered and important role The importance of the registration of VAT documents confirm the limit, right, tax obligations of businesses active businesses, manufacturing, trade, service correct sector professionals has received over a reference verification monitoring, notification given tax each of the businesses doing business in the capital, some on the approval of The water tax.The government of Laos has promoted the domestic production, attract investors, both domestic and foreign confidence further, the government should improve tax value and tax types to ensure effective implementation of laws tax increase use and management of income tax into development of the economy of the country as well as the A step.